Effect of Photocatalysts Preparation Methods and Light Source on Orange II Photocatalytic Degradation - Riaz, Nadia (IACSIT Press, Singapore, 2011)
The objective of the present work was to synthesize 10 wt % metal doped TiO2 (Degussa P-25) photocatalysts using three methods: complex precipitation (CP), depositionprecipitation (DP) and wet impregnation (WI) methods and to evaluate their performance for a model azo dye, Orange II. The raw photocatalysts were activated by calcination at three different temperatures (180°C, 200°C and 300°C) for 1 hour duration. Photocatalytic degradation for 50 ppm orange II was studied at pH 6.8 under the irradiation of a UV light and visible light. The extent of dye degradation was determined using UV-vis Spectrophotometery. On the basis of results it was observed that visible light has better effect for dye removal compared to UV light and WI photocatalysts showed the best decolorization results with 100% Orange II removal for photocatalysts calcined at 1800C and 2000C while 98.5% for 3000C calcination temperature. Selected photocatalysts were characterized using Powder X-ray Diffraction (XRD), Fieldemission Scanning Electron Microscopy-Energy Dispersive Xray (FESEM- EDX) and Diffuse Reflectance UV visible spectroscopy (DRUV vis).